Transmission Route of Airborne Fungal Spores for Cucumber Downy Mildew - Yafei Wang; Qiang Shi; Guilin Xu; Ning Yang; Tianhua Chen; Mohamed Farag Taha; Hanping Mao (Horticulturae)
Analyzing the transmission dynamics of airborne disease spores is crucial for advancing early warning and control strategies for crop diseases. This study introduces a novel approach utilizing the HYSPLIT-5 model to investigate the spore transmission patterns and pathways of airborne crop diseases. By employing the Lagrangian particle trajectory method of HYSPLIT-5 in conjunction with MeteInfoMap 3.5, the spatiotemporal frequency of cucumber downy mildew spore trajectories over extended periods was examined. The results indicate that the transmission trajectory of cucumber downy mildew spores is heavily influenced by atmospheric circulation, with spores spreading along air currents to surrounding areas. These trajectories frequently intersect, resulting in a broad transmission range, and the observed transmission patterns exhibit a degree of universality. Which provided a basis for the subsequent study of a large-scale prediction model of cucumber downy mildew.